Bluff body drag manipulation using pulsed jets and Coanda effect. (20th September 2016) - Barros, Diogo; Borée, Jacques; Noack, Bernd R.; Spohn, Andreas; Ruiz, Tony
Abstract : The impact of fluidic actuation on the wake and drag of a three-dimensional blunt body is investigated experimentally. Jets blowing tangentially to the main flow force the wake with variable frequency and amplitude. Depending on the forcing conditions, two flow regimes can be distinguished. First, in the case of broadband actuation with frequencies comprising the natural wake time scale, the convection of the jet structures enhances wake entrainment, shortens the length of the recirculating flow and increases drag. Secondly, at higher actuation frequencies, shear-layer deviation leads to fluidic boat tailing of the wake. It additionally lowers its turbulent kinetic energy thus reducing the entrainment of momentum towards the recirculating flow. The combination of both mechanisms produces a rise in the base pressure and reduces the drag of the model. Both actuation regimes are characterized by complementary velocity, pressure and drag measurements at several upstream conditions and control parameters. By adding curved surfaces to deviate the jets by the Coanda effect, periodic actuation is reinforced and drag reductions of approximately 20 % are achieved. The unsteady Coanda blowing not only intensifies the flow deviation and the base pressure recovery but also preserves the unsteady high-frequency forcing effect on the turbulent field. The present results encourage further development of fluidic control to improve the aerodynamics of road vehicles and provide a complementary insight into the relation between wake dynamics and drag.